Effects of human growth hormone on gonadotropin-releasing hormone neurons in mice - Janardhan P. Bhattarai; Shin Hye Kim; Seong Kyu Han; Mi Jung Park (Korean Pediatric Society, 2010)
PurposeRecombinant human growth hormone (rhGH) has been widely used to treat short stature. However, there are some concerns that growth hormone treatment may induce skeletal maturation and early onset of puberty. In this study, we investigated whether rhGH can directly affect the neuronal activities of of gonadotropin-releasing hormone (GnRH).MethodsWe performed brain slice gramicidin-perforated current clamp recording to examine the direct membrane effects of rhGH on GnRH neurons, and a whole-cell voltage-clamp recording to examine the effects of rhGH on spontaneous postsynaptic events and holding currents in immature (postnatal days 13-21) and adult (postnatal days 42-73) mice.ResultsIn immature mice, all 5 GnRH neurons recorded in gramicidin-perforated current clamp mode showed no membrane potential changes on application of rhGH (0.4, 1 µg/mL). In adult GnRH neurons, 7 (78%) of 9 neurons tested showed no response to rhGH (0.2-1 µg/mL) and 2 neurons showed slight depolarization. In 9 (90%) of 10 immature neurons tested, rhGH did not induce any membrane holding current changes or spontaneous postsynaptic currents (sPSCs). There was no change in sPSCs and holding current in 4 of 5 adult GnRH neurons.ConclusionThese findings demonstrate that rhGH does not directly affect the GnRH neuronal activities in our experimental model.